2009
DOI: 10.1002/btpr.371
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐based alkali pretreatment of switchgrass and coastal bermudagrass for bioethanol production

Abstract: Switchgrass and coastal bermudagrass are promising lignocellulosic feedstocks for bioethanol production. However, pretreatment of lignocelluloses is required to improve production of fermentable sugars from enzymatic hydrolysis. Microwave‐based alkali pretreatment of switchgrass and coastal bermudagrass was investigated in this study. Pretreatments were carried out by immersing the biomass in dilute alkali reagents and exposing the slurry to microwave radiation at 250 W for residence times ranging from 5 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(80 citation statements)
references
References 37 publications
6
73
0
1
Order By: Relevance
“…It can be observed that more severe pretreatment with higher NaOH concentration cause greater disruption on the fiber structure and creating number of large pores. This phenomenon significantly increases the accessibility of enzyme during hydrolysis process [3]. After the enzymatic hydrolysis, the structure mesocarp fiber was completely destroyed and wall of the fibers was completely ruptured as shown in Fig.…”
Section: Overall Conversion Of Carbohudrates In Opmfmentioning
confidence: 86%
See 1 more Smart Citation
“…It can be observed that more severe pretreatment with higher NaOH concentration cause greater disruption on the fiber structure and creating number of large pores. This phenomenon significantly increases the accessibility of enzyme during hydrolysis process [3]. After the enzymatic hydrolysis, the structure mesocarp fiber was completely destroyed and wall of the fibers was completely ruptured as shown in Fig.…”
Section: Overall Conversion Of Carbohudrates In Opmfmentioning
confidence: 86%
“…Due to the enormity of the plantation industry, about 10.9 million tons of oil palm mesocarp fiber is being produced annually as agriculture waste and contributes to the accumulation of lignocellulosic waste and cause emission of greenhouse gas to the environment [1]. Traditionally oil palm mesocarp fiber is either used in mulching or incinerated, however both Manuscript received February 9, 2013; revised April 12, 2013 Generally, lignocellulosic biomass consists of three main groups of polymer that are cellulose, hemicelluloses and lignin [3]. These compounds are also major components in oil palm biomass [4].…”
Section: Introductionmentioning
confidence: 99%
“…Switchgrass is recognized as a desirable energy crop due to high productivity, low agricultural inputs for harvest, and protection of the environment [29]. Corn stover, consisting of stalks, cobs and leaves that remain in fields after the gain harvest, has a carbohydrate content of approximately 60% of the dry weight [30].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study, microwave-based alkali pretreatment of switchgrass and coastal bermudagrass resulted in better sugar yields during subsequent enzymatic hydrolysis; as high as 82% glucose and 63% xylose yields for switchgrass and 87% glucose and 59% xylose yields for Bermuda grass were reported [38].…”
Section: Pretreatment Of Biomassmentioning
confidence: 83%
“…Microwave irradiation of biomass is a promising pretreatment process because it utilizes thermal and specific (non-thermal) effects generated by microwaves in aqueous environments [38]. Low temperature pretreatment is generally preferred to avoid hemicellulose degradation and to improve the pentose yield [39].…”
Section: Pretreatment Of Biomassmentioning
confidence: 99%